Corporate Entrepreneurship at Toserba Yogya as A Driver of Innovation in the Face of Digitalization - Nurhadi, Dhifan Fadhilah Rizky; Purbasari, Ratih; Purnomo, Margo (Indo Consultan Energi, 2025)
This study investigates the impact of Corporate Entrepreneurship on driving innovation and facilitating digital adaptation at PT Akur Pratama (Toserba Yogya), a leading player in Indonesia's retail industry. Using a descriptive qualitative method, the research draws on secondary data sources such as academic books, scientific journals, media articles, and company reports. This approach provides an in-depth understanding of how Corporate Entrepreneurship has been employed to enhance Toserba Yogya's operational efficiency, customer-oriented innovation, and market competitiveness through digital initiatives like e-commerce and mobile applications. The findings reveal that Corporate Entrepreneurship has significantly bolstered the company's ability to navigate the digital transformation, resulting in improved performance, higher customer satisfaction, and industry recognition with Superbrand Indonesia and Top Brand Award awards. The study underscores the role of continuous innovation and adaptation in maintaining competitiveness and achieving sustainable growth in the evolving retail landscape.